Development of a Deoxygenative Ring Contraction Reaction for Nitrogen Heterocycle Synthesis - Atkinson, Nick (2023)
Small nitrogen-containing saturated heterocycles are ubiquitous motifs found in a vast number of organic molecules that include natural products, active pharmaceuticals and agrochemicals. Hence, inexpensive, accessible and practical strategies for making these heterocycles is of great interest to the chemical industry. Fortunately, deoxygenative ring contractions provide a novel way of synthesising substituted amines of this type that would otherwise be very hard to obtain by classical synthesis methods. 3,6-Dihydro-2H-1,2-oxazines can be valuable synthesis precursors to highly functionalised heterocycles. Hence, they constitute attractive starting points for the synthesis of unsymmetrical substituted 3-pyrrolines and pyrrolidines that would represent challenging targets using more conventional strategies.